Peningkatan Kendali Mutu Audit Inspektorat Utama BPS RI Modul Perencanaan dan Pelaksanaan Audit Melalui Pembangunan Sistem Informasi - Fajar, Roby Awaludin; Maghfiroh, Lutfi Rahmatuti (Politeknik Statistika STIS, 2024)
Statistics Indonesia (BPS) is mandated to perform internal supervision to ensure organizational purposes and functions adhere to good governance standards. This supervision is conducted by the Main Inspectorate, responsible for audit activities.Currently, audit documentation fails to fully comply with quality control standards and the manual audit process induces inefficiencies in data entry and document management. Consequently, this study aims to enhance audit quality control through the development of an information system utilizing the modified waterfall SDLC model. Business process data were collected through interviews and literature reviews.The system was tested using black-box testing and evaluated with Computer System Usability Questionnaire (CSUQ). Results indicated that all system features functioned as specified, with high scores in all CSUQ categories. User evaluations demonstrated that the system effectively improves transparency, accountability, and efficiency, ensures information is displayed according to access rights, produces accurate documentation, and facilitates the input and storage of audit records.